2011
DOI: 10.1021/es103381y
|View full text |Cite
|
Sign up to set email alerts
|

Polar Compounds Dominate in Vitro Effects of Sediment Extracts

Abstract: Sediment extracts from three polluted sites of the river Elbe basin were fractionated using a novel online fractionation procedure. Resulting fractions were screened for mutagenic, aryl hydrocarbon receptor (AhR)-mediated, transthyretin (TTR)-binding, and estrogenic activities and their potency to inhibit gap junctional intercellular communication (GJIC) to compare toxicity patterns and identify priority fractions. Additionally, more than 200 compounds and compound classes were identified using GC-MS/MS, LC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 43 publications
4
50
0
1
Order By: Relevance
“…All these classes of compounds have also been found in the aromatic UCM fraction in UK estuary sediments, and several of them have been tested positive for mutagenic activity [35]. Some of the compounds identified with GCxGC-ToF-MS are known agonists of the AhR, for example 11H-benz(a)fluoren-11-one, 11H-benz(b)fluoren-11-one [36], methylpyrene and methylchrysene [37,38]. Others, like carbazole and dibenzothiophene, are CYP1A1 inhibitors [39], and these compounds can, to some extent, contribute to the total AhR activity of the samples.…”
Section: Particle Fractionmentioning
confidence: 99%
“…All these classes of compounds have also been found in the aromatic UCM fraction in UK estuary sediments, and several of them have been tested positive for mutagenic activity [35]. Some of the compounds identified with GCxGC-ToF-MS are known agonists of the AhR, for example 11H-benz(a)fluoren-11-one, 11H-benz(b)fluoren-11-one [36], methylpyrene and methylchrysene [37,38]. Others, like carbazole and dibenzothiophene, are CYP1A1 inhibitors [39], and these compounds can, to some extent, contribute to the total AhR activity of the samples.…”
Section: Particle Fractionmentioning
confidence: 99%
“…Wang et al (2011a) reported that the direct acting mutagenicity of Beijing particulate matter (PM) caused by the OPAHs and NPAHs was 2 times higher than that of the indirect mutagenicity caused by the PAHs, though the OPAH and NPAH concentrations only contributed 8% to the total PAH concentrations. In polluted river sediment, the fraction of the extracts containing the polar PAHs (including NPAHs) showed higher toxicities than those containing the non-polar PAHs like PAHs (Lübcke-von Varel et al, 2011). The OPAHs were weak inducers of in vitro estrogenic activity, similar to that of benzo [a]pyrene in river sediments (Machala et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…While NPAHs were not detected in pond stations in the Twin Cities, MN, metropolitan area (Crane, 2014), NPAHs including 2-nitrofluorene, 1-nitropyrene and 6-nitrochrysene were detected at ppb to ppm levels in Varney Pond, White Bear Lake, MN (MDH, 2011). In Europe, NPAHs including nitronaphthalenes, 9-nitronaphthalene, 1-nitropyrene, 6-nitrochrysene and dinitropyrenes have been found at ppb levels in sediments from the Elbe River basin, Germany and Czech Republic (Lübcke-von Varel et al, 2012; Lubcke-von Varel et al, 2011). In sediments of the Suimon River, Japan, 1-nitropyrene and 2-nitrofulorene were measured at ppb levels (Sato et al, 1985).…”
Section: Introductionmentioning
confidence: 99%